ANALISIS TINDAK TUTUR KESANTUNAN PEDAGANG DAN PEMBELI DI PASAR GOTONG ROYONG PROBOLINGGO - Kholik Kholik (LP3M IAI Al-Qolam Malang, 2017)
In the speech acts of traders and buyers in the market, there is the principle of politeness. In the buying and selling activities both parties try to be polite to the speech partners. With the politeness of the merchants and the buyers, they expect a sale and purchase of merchandise. The problem of this study is: how is the maximized description of wisdom, generosity, appreciation, simplicity, consensus, and the conclusions of merchants and buyers in Gotong Royong Market of Probolinggo? It is a qualitative descriptive analysis of pieces of speech that contains the principles of politeness taken from traders and buyers. The instrument validity uses data recording devices and data cards. The result of this study states that the speech acts of merchants and buyers in the market Gotong Royong Probolinggo sufficiently pay attention to the principle of politeness. This is evident from the process of analysis of the six maxims of politeness. Both the traders and the buyers in the market pay attention to these maxims to establish a good relationship between them in order to make a pleasant sale and purchase transactions without any gaps and misunderstandings. Keywords: Speech acts, Politeness, Merchants, Buyers